Corporate Learning with Moodle Workplace : Explore concepts, implementation, and strategies for adopting Moodle Workplace in your organization /: Explore concepts, implementation, and strategies for adopting Moodle Workplace in your organization. (2020) - Büchner, Alex
No abstract available